2008
DOI: 10.1007/s11655-008-0173-6
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Chinese Quality of Life Instrument in patients with congestive heart failure

Abstract: The ChQOL was better in sensitivity and responsiveness for assessing congestive heart failure as a generic measure than the SF-36 and WHOQOL-BREF. The ChQOL is considered suitable as an outcome measure for clinical trials in patients with congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The 6‐item EQ‐5D was used to assess health status in five dimensions, including the mobility, self‐care, usual activities, pain/discomfort and anxiety/depression 15 . Cronbach's α for the EQ‐5D was 0.761.…”
Section: Methodsmentioning
confidence: 99%
“…The 6‐item EQ‐5D was used to assess health status in five dimensions, including the mobility, self‐care, usual activities, pain/discomfort and anxiety/depression 15 . Cronbach's α for the EQ‐5D was 0.761.…”
Section: Methodsmentioning
confidence: 99%
“…Medicine and proved to be a well validated generic, self-reported health status instrument [34]. It has been used with Chinese HF patients [35,36]. A small study of 39 in-patients with congestive HF who had undergone treatment with integrative Chinese medicine found that all domains of the ChQoL showed significant improvement after treatment, and the ChQoL was demonstrated to be more responsive to measuring changes in quality of life than two generic questionnaires -World Health Organisation Quality of Life assessment short form (WHOQOL-BREF) and the Short Form 36-item Health Survey (SF-36), but less responsive than the disease-specific questionnaire -MLHFQ [36].…”
Section: Chqol Was Initially Developed Based On the Concept Of Healthmentioning
confidence: 99%
“…It has been used with Chinese HF patients [35,36]. A small study of 39 in-patients with congestive HF who had undergone treatment with integrative Chinese medicine found that all domains of the ChQoL showed significant improvement after treatment, and the ChQoL was demonstrated to be more responsive to measuring changes in quality of life than two generic questionnaires -World Health Organisation Quality of Life assessment short form (WHOQOL-BREF) and the Short Form 36-item Health Survey (SF-36), but less responsive than the disease-specific questionnaire -MLHFQ [36]. Although these results suggest that the ChQoL could be considered suitable as an outcome measure for Chinese patients with congestive HF, it may be impractical given the complexity of the questionnaire: 50 items across physical/spiritual/emotional domains which require 10 -20 minutes to complete.…”
Section: Chqol Was Initially Developed Based On the Concept Of Healthmentioning
confidence: 99%
“…The WHOQOL-BREF provides a shorter instrument and being, theoretically, more manageable (Garcia-Rea & LePage, 2010). The WHOQOL-BREF has been tested in numerous populations including geriatric (Chachamovich et al, 2008), transplants (Nejatisafa et al, 2008), anxiety and depression (Masskulpan et al, 2008), cognitive impairment (Kim et al, 2008), heart failure (Zhao et al, 2008), multiple sclerosis (Wynia et al, 2008) and homeless veteran (Garcia-Rea & LePage, 2010). In brief, the instrument has four domains: Physical Health, Psychological, Social Relationship, and Environment.…”
Section: Introductionmentioning
confidence: 99%